Hybridization as a technique of biological evolution (1973)
The hybridization of two species represents a method of more importance in obtaining the understanding of the relationships of these species.  The crosses in vitro avoid the operation of the mechanisms that are aislated, as the characteristics of the mating call and the size of the body. The results of these crosses provide an indication of the degree of affinity of the species. It is possible, naturally, that a singular gene canprovide an obstacle for the crossing of two species, but the results of numerous crosses indicate that many genes involve themselves in the obstacles of crossing of the two species. Consequently, the results of the crosses permit the reconstruction of the evolutionary history of the groups. No method is of more importance with respect to this type of information than the hybridization method.